2023
DOI: 10.3390/w15040736
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Background Water Leaks Using a High-Resolution Dyadic Transform

Abstract: This article solves the problem of detecting water leaks with a minimum size of down to 1 mm in diameter. Two new mathematical tools are used to solve this problem: the first one is the Te cross-spectral density and the second is Te coherence. These mathematical tools provide the possibility of discriminating spurious frequency components, making use of the property of multi-sensitivity. This advantage makes it possible to maximize the sensitivity of the frequency spectrum. The wavelet function used was Daubec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Furthermore, the fifth contribution demonstrates the existence of the inverse T e transform, and lastly, the sixth contribution provides a uniqueness theorem for the T e transform. The theoretical results presented in this paper were validated by the authors of the works shown in [1][2][3][4].…”
Section: Introductionmentioning
confidence: 52%
See 2 more Smart Citations
“…Furthermore, the fifth contribution demonstrates the existence of the inverse T e transform, and lastly, the sixth contribution provides a uniqueness theorem for the T e transform. The theoretical results presented in this paper were validated by the authors of the works shown in [1][2][3][4].…”
Section: Introductionmentioning
confidence: 52%
“…Only when compacting its output information is it observed how the frequency is scaled by a dyadic factor. Previous research conducted by the authors of this paper demonstrates that such scaling enables the isolation of frequency components, the attenuation of cross-terms, and the identification of system behaviors [1][2][3][4].…”
Section: Definition 1 (T E Window)mentioning
confidence: 91%
See 1 more Smart Citation
“…For the T e -gram definition in Section 3, it is necessary to start from the definition of the T e Transform given by the authors in [4,32]. It is also required for the analysis of the seismic signal that will be developed in Section 5.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The T e Transform defined by [4,32] is a mathematical tool that allows for obtaining a dyadic frequency spectrum. Its main advantage is that it allows the isolation of spurious frequency components.…”
Section: T E Transformmentioning
confidence: 99%